A dual-purpose solar collector as a parallel flow heat exchanger: A novel mathematical framework - Mustafa Moayad Hasan; Krisztián Hriczó (International Journal of Thermofluids)
The solar thermal system is a crucial segment of solar energy technologies. Maximizing the efficiency of the collector contributes significantly to boosting the entire performance of solar thermal systems. Among them, a dual-purpose solar collector, which fulfills the bi-function of producing hot water and air concurrently, is particularly important. Maximizing the efficiency of such a collector remains a significant challenge that affects overall energy utilization. In this research, the dual-purpose solar collector was treated as a parallel flow heat exchanger, and a unique mathematical analysis was developed using the effectiveness-number of transfer unit approach. This innovative approach applies a well-established equation from the realm of parallel flow heat exchangers to this new context, which has not been previously explored in the literature. To ensure the reliability and robustness of the suggested model, the obtained results were compared with experimental data from existing studies, focusing on two key metrics: relative percentage error and average relative percentage error. The analysis yielded a relative percentage error of 2.94% and an average relative percentage error of 1.3%. These metrics fall within acceptable limits, indicating a strong correlation between the predictions made by the suggested model and the experimental observations available in the literature. The developed mathematical model demonstrates an accurate prediction of dual-purpose solar collector performance, providing researchers with a reliable tool for evaluating the suitability of these systems for a range of applications.